UNESCO Global Geopark Biokovo–Imotski Lakes: Potential Contribution to the Enhancement of Tourism in the Imotski Region - Karamehmedović, Deša; Kolovrat, Luka (Oeconomica Jadertina, 2026)
The purposes of the research were to determine the expected benefits of the designation of the Biokovo-Imotski Lakes Geopark (BILUGGp) as a UNESCO Global Geopark for tourism development in the Imotski Region, and the expected benefits of partnership programmes with the Geopark. The paper also reviews of examples of good practices from selected UNESCO Global Geoparks, highlighting projects and activities that could be adapted to support BILUGGp. Empirical research using the e-Delphi technique was employed to investigate the mentioned topic, in conjunction with online research regarding UNESCO Global Geoparks, pertinent documents, as well as scientific and professional literature. Data: The internet survey covered 213 UNESCO Global Geoparks, i.e., their websites, located in 48 countries, and 27 panellists ultimately participated in the e-Delphi survey. Results show the expected benefits of this designation for the tourism development of the Imotski Region include a substantial increase in the destination’s visibility (37%), the promotion of new tourist facilities (33%), and the establishment of conditions favorable for geotourism development (32%). 2) The expected benefits arising from partnership programs with the Geopark are evident in collaboration with other Geoparks on particular projects (such as Geofood) (37%), enhanced overall promotion (30%), and greater visibility for stakeholders (26%). The designation of Geopark offers numerous benefits and opportunities for growth across the entire region, which encompasses Imotski, Biokovo, Zabiokovlje, and the Makarska Riviera. It promotes the development of tourism, enhances geotourism and destination branding, encourages collaboration with other Geoparks, and supports the development of agriculture, hospitality, trade, and services. Furthermore, it stimulates the revitalization of traditional crafts and customs, establishes a variety of partner programs, advocates for the sustainable management of both natural and cultural heritage, and contributes positively to the well-being of the local community.
Keywords: UNESCO Geoparks, Biokovo-Imotski Lakes Geopark, tourism development, benefits, partnership